Pengembangan Game Edukasi Eng-Joy Menggunakan Construct2 pada Mata Pelajaran Bahasa Inggris Kelas X - Rahmi, Latifa; Amilia, Winanda; Zen, Zelhendri; Anugrah, Septriyan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by the results found in the field that there are students who still have difficulty in understanding the sentences in the narrative text, especially when there are commands to connect or replace simple past and simple present tense verbs. Then during the teaching and learning process, the teacher still uses media that is not varied. So it takes media that can make students interested in participating in learning in class and one of them uses educational games. This study aims to produce educational games in English Class X subjects that are valid and practical using the type of Research and Development (R&D) research, the 4D development model consisting of define, design, development, and disseminate. At the validity test stage, it was carried out with 2 stages of validation, namely material validity, and media validity, while at the product trial stage it was carried out on 34 class X students at MAN 1 Padang City with the aim of knowing the practicality of the product developed. The results of the research conducted explained that the product developed was “Very Valid”, then the results of material validation were declared “Very Feasible”. While the results of practicality from students were declared “Very Practical”, thus this Eng-Joy educational game is practical and feasible to use in the learning process in Grade X English Subjects